Online Identity Analysis of Public Figure Habib Jafar: Analisis Identitas Daring Tokoh Publik Habib Jafar - Deviyanti, Wida; Salsabillah, Chorida Fara (Universitas Muhammadiyah Sidoarjo, 2025)
A well-known public figure in Indonesia, Habib Husein Ja'far Al Hadar is recognized for his inclusive and contemporary approach to preaching. His presence on social media has sparked numerous debates and conflicts, while also creating a distinctive online persona that captures attention. This analysis will explore how Habib Husein Ja'far has built his unique online identity, managed interactions with diverse audiences, and addressed the challenges posed by online disputes and attacks. The findings suggest that while Habib Husein Ja'far has successfully established a significant online presence, there is a need for government regulation to mitigate the dangers posed by online conflicts and harassment. Highlights: Unique Online Identity – Habib Husein Ja'far blends traditional Islamic teachings with modern, inclusive messaging, making his presence distinct and engaging on social media. Audience Engagement & Conflict Management – He navigates diverse audience interactions skillfully, addressing criticisms while maintaining his message of tolerance. Regulation & Online Safety – The rise of online conflicts and harassment in religious discourse highlights the need for government oversight to ensure a safer digital space. Keywords: Habib Husein Ja'far, Online Persona, Social Media, Online Conflicts, Government Regulation